Resolusi Konflik Petani Sekitar Perkebunan Karet melalui Pengembangan Modal Sosial di Desa Kuto Kecamatan Kerjo Kabupaten Karanganyar - D Padmaningrum; Sutarto Sutarto; Agung Wibowo (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The majority of local population living close to the rubber plantation are farmers. Some of them lived under the proverty line. The management of rubber estate, in fact, ignored local culture. Both situation, the proverty and lack of corporates social responsibility caused intensive conflicts. The objectives of this research  describe: the factors fromulated social capital’s value and the role of social capital in conflict resolution in rubber estate. The constituants of the conflict consist of: the management of rubber estate, internal staff, the local people, local leaders also local and outside traders. This conflict involved: encrochment for agriculture, collecting fire woods illegally and stone mining illegally. In this case, the role of social capital values can described by many activities. The management is required to consider the aspirations of local people and to develop social network between the rubber estate with the local community; in particulary with local leaders; to develope the good exchange with local community, especially funds for social funtions; recruitment of the local people to work in the plantation; supply fresh water; all of which is aplication of the Corporate Social Responsibility (CSR) of the rubber estate. In the mean time, the local people are requested to participate in the maintenance and sustainability of the rubber estate